2014
DOI: 10.1016/j.legalmed.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Y chromosome haplogroups in Japanese population using short amplicons and its application in forensic analysis

Abstract: Analysis of Y chromosome haplogroups in Japanese population using short amplicons and its application in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The haplogroup O1b2a1a1 was the most dominant, and C1a1, C2, D1a2a-M55, D1a2a-12f2b, O1b2, O2a2b1, and O2a1b had frequencies > 5% among the participants. The frequency distributions of the subjects was similar to those of other cohorts (8)(9)(10)(11). The means and standard deviations of birth weight and height for each haplotype are also shown in Table 1.…”
Section: Y Chromosome Haplogroups and Birth Height And Weight In Japa...supporting
confidence: 74%
“…The haplogroup O1b2a1a1 was the most dominant, and C1a1, C2, D1a2a-M55, D1a2a-12f2b, O1b2, O2a2b1, and O2a1b had frequencies > 5% among the participants. The frequency distributions of the subjects was similar to those of other cohorts (8)(9)(10)(11). The means and standard deviations of birth weight and height for each haplotype are also shown in Table 1.…”
Section: Y Chromosome Haplogroups and Birth Height And Weight In Japa...supporting
confidence: 74%
“…To improve the usefulness of the systems for analyzing degraded DNA samples, we designed primers to render amplicons of 150 bp or shorter. This stems from the fact that past research has already shown that DNA fragmentation is a major obstacle in analyzing degraded DNA samples, and because in STR analysis, we obtained extremely useful results with amplicons 150 bp or smaller . In the assay of the Jomon skeleton, c .260 bp region in the HVS1 failed to be amplified.…”
Section: Resultsmentioning
confidence: 91%